The effectiveness of isometric knee exercises as a non-pharmacological therapy for pain reduction in knee osteoarthritis: A systematic review - Primanita Ulfah; Arif Setyo Upoyo (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Pain, stiffness, and decreased mobility are the main symptoms of osteoarthritis (OA), a degenerative joint disease that mostly affects the knee. The increasing prevalence of OA worldwide highlights the necessity of efficient non-pharmacological management techniques. Purpose: To evaluate the effectiveness of isometric knee workouts in enhancing functional results and reducing pain in individuals with osteoarthritis. Method: A comprehensive search was conducted using Google Scholar, PubMed, ScienceDirect, and ProQuest to find publications published between 2014 and 2024. The inclusion criteria focused on studies that used isometric exercises as an intervention for knee OA. The Critical Appraisal Skills Program of the Joanna Briggs Institute (JBI) was used to assess the quality of the selected publications. Data were analyzed thematically to compile conclusions on pain alleviation and functional enhancement. Results: Eleven studies totaling 876 participants were included in the review. The treatments, which lasted anywhere from four to twelve weeks, continuously showed notable improvements in joint function and pain reduction. Results were improved by using isometric exercises both on their own and in conjunction with treatments like ultrasound and biofeedback. The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), the Visual Analog Scale (VAS), and the Numerical Rating Scale (NRS) were frequently used to measure pain. Despite certain constraints, such as small sample sizes and brief follow-up periods, the quality assessment showed that the majority of studies had excellent methodological rigor. Conclusion: For individuals with knee OA, isometric knee exercises are useful in lowering discomfort and enhancing functional results. The effectiveness of these exercises can be further increased by combining them with biofeedback or other therapeutic methods. These results provide a useful, low-risk strategy for enhancing patient quality of life and support the incorporation of isometric exercises into non-pharmacological therapy options for knee OA.